Applying nursing process : a tool for critical thinking - Alfaro-LeFevre, Rosalinda (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
'Applying Nursing Process' presents an overview of the nursing process, clarifies the staff nurse's responsibilities, and promotes critical thinking in a range of clinical practice settings through case examples and real-life scenarios.
Nursing process overview -- Assessment -- Diagnosis -- Planning -- Implementation -- Evaluation --
Includes index.
Keywords: NURSING -- HANDBOOKS, MANUALS, ETC